Strategi Melayani Unreached People Groups Berdasarkan Kajian Eksegetis 1Korintus 9: 19-23 - Samuel Purdaryanto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
This theme discusses the exegetical study of contextual evangelism in 1 Corinthians 9: 19-23. Contextual evangelism has always been an interesting topic in discussions of Missiology and Ecclesiology. Although sometimes controversy, contextual evangelism is still one of the effective methods of preaching the gospel to the neglected tribes. The preaching of the cross-cultural gospel was one of the points Paul talked about with the church in the city of Corinth. The Apostle Paul said that preaching the gospel was a must for him (1 Corinthians 9:16). And in chapters 9: 19-23 the apostle Paul tells how the method or method he used to preach the gospel to those who are culturally different from himself. Gospel preaching is a mandate or the Great Commission given by the Lord Jesus to believers, and must be preached to all tribes and languages. In preaching the Gospel, Paul sets an example that is a strategy in contextual evangelism. The Apostle Paul willingly devoted himself